Inhibition of Enterovirus 71 Replication by 7-Hydroxyflavone and Diisopropyl-Flavon7-yl Phosphate - Wang, Jianmin (Public Library of Science, 2014)
Enterovirus 71 (EV71) is the major causative agent of hand, foot, and mouth disease, which has been continuously prevalent in Asia in recent years. In children, severe cases can lead to death, and no prophylactic or therapeutic measures against EV71 infection are available. The 3C proteases of EV71 play an important role in viral replication and are an ideal drug target. In previous work, we resolved the crystal structure for EV71 3C(pro). In this report, we took advantage of the automated docking program AutoDock 4.0 to simulate EV71 3C(pro)-ligand conformation. 7-hydroxyflavone (HF) and its phosphate ester(FIP) were predicted to bind with EV71 3C(pro).In an in vitro protease inhibition assay, FIP inhibited EV71 3C(pro) protease activity. Both flavones were highly active against EV71, protecting cells from EV71 infection. Replication of viral RNA and formation of EV71 plaque were all strongly inhibited in cells. These results indicated that HF and FIP may serve as potential protective agents in the treatment of patients with chronic EV71 infection.